2017
DOI: 10.3892/etm.2017.5348
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of percutaneous endoscopic lumbar discectomy on lumbar disc herniation and its effect on oxidative stress in patients with lumbar disc herniation

Abstract: This study investigated the therapeutic effect of percutaneous endoscopic lumbar discectomy on lumbar disc herniation, and explored its effect on oxidative stress in patients with lumbar disc herniation. One hundred and ten patients with lumbar disc herniation were selected in The Affiliated People's Hospital of Shanxi Medical University from May 2015 to May 2016. Patients were divided into control group (n=50) and observation group (n=60) according to different surgical methods. Patients in control group were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Another interesting finding of this study was that patients in minimally invasive group had lower levels of postoperative inflammatory response and faster immune function recovery. Chang et al (22) drew similar conclusions in their study. The levels of inflammatory factors TNF-α and CRP in patients undergoing percutaneous endoscopic lumbar discectomy were also significantly lower than those in patients undergoing open discectomy.…”
Section: Discussionsupporting
confidence: 68%
“…Another interesting finding of this study was that patients in minimally invasive group had lower levels of postoperative inflammatory response and faster immune function recovery. Chang et al (22) drew similar conclusions in their study. The levels of inflammatory factors TNF-α and CRP in patients undergoing percutaneous endoscopic lumbar discectomy were also significantly lower than those in patients undergoing open discectomy.…”
Section: Discussionsupporting
confidence: 68%
“…During the follow-up, the clinical outcomes were better in the PELD group, and the levels of C-reactive protein, creatine phosphokinase, and interleukin 6 were all lower in the PELD group than in the OD group. Another study showed similar results [21]; however, opposite results have also been reported [22]. PELD was considered less invasive to soft tissue and with a faster recovery.…”
Section: Discussionmentioning
confidence: 58%
“…Eight studies reported the data of recurrence rate. [ 44 , 45 , 47 50 , 54 , 56 ] The recurrence rates in the PELD and other surgical intervention groups were 7.57% and 4.38%, respectively. The aggregated results of these studies suggested that PELD was associated with a significantly higher recurrence rate than other surgical interventions (RR = 1.65, 95%CI: 1.08, 2.52; P = .021) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ten of the included trials in the present study were of cohort design, [ 44 47 , 50 , 52 54 , 56 , 57 ] and 4 were RCT design. [ 48 , 49 , 51 , 55 ] Among the included studies, four compared PELD with OLM, [ 44 , 46 , 47 , 50 ] three compared PELD with MIS-TLIF, [ 45 , 52 , 54 ] three compared PELD with MED, [ 45 , 55 , 57 ] three compared PELD with microsurgical discectomy, [ 48 , 49 , 51 ] one compared PELD with open discectomy, [ 56 ] and one compared PELD with fenestration discectomy. [ 53 ] Most of the included studies enrolled adult patients with a mean age between 33.1 and 57.2 years, whereas in the study of Ahn SS, et al, [ 47 ] they enrolled young adults with an age between 20–25 years.…”
Section: Resultsmentioning
confidence: 99%